PERANCANGAN REPOSITORI DIGITAL UNTUK MENINGKATKAN EFEKTIVITAS PENGELOLAAN LAPORAN PESERTA PELATIHAN (STUDI KASUS PADA PUSAT PEMBELAJARAN DAN STRATEGI KEBIJAKAN MANAJEMEN PEMERINTAHAN) - Setiawan, Fhajar; Chairunisa, Frida (Politeknik STIA LAN Makassar, 2025)
The success of an organization is highly influenced by the effectiveness of human resource management, including in the management of information and public services. At the Library of the Center for Learning and Public Management Policy Strategy, the management of Civil Service Candidate (CPNS) actualization reports is handled by only one staff member. Meanwhile, the number of reports continues to increase each year in line with the growing number of training participants. This imbalance has caused the classification and access process of reports to become inefficient and prone to accumulation. The purpose of this study is to design a digital system called the Repository of Civil Service Candidate Actualization Reports (Relasi CPNS). Based on data collected through interviews, observations of management activities, and document analysis of the number of reports stored in the library, the researcher designed a digital system called the Repository of Civil Service Candidate Actualization Reports (Relasi CPNS). To measure the effectiveness of the designed system, the researcher conducted a trial involving both administrator and user roles through direct access to the platform accompanied by usage guidelines and feedback questionnaires. The trial results showed that all features in Relasi CPNS functioned properly, were well-integrated, and supported the workflow of each role. This system can be utilized for more efficient report management and easier access to digital information, thereby potentially reducing the manual workload that has so far been handled by a single staff member